Jennifer L. Andruska, Wise and Foolish Love in the Song of Songs (Oudtestamentische Studiën 75; Leiden – Boston, MA: Brill 2018). Pp. 219. €104. ISBN 978-90-04-33101-3 (e-Book) - Bardski, Krzysztof (The Biblical Annals, 2021)
Book Review: Jennifer L. Andruska, Wise and Foolish Love in the Song of Songs (Oudtestamentische Studiën 75; Brill: Leiden-Boston 2018)